Peran Kelembagaan Komunitas Petani Sawah Tadah Hujan di Kabupaten Lampung Selatan - Siti Mariyani; Nurmala K. Pandjaitan; Martua Sihaloho (Program Studi Agribisnis, Fakultas Pertanian, Universitas Singaperbangsa Karawang, 2022)
Rainfed rice farming communities feel the impact of climate change because they rely on rainfall as the main source of agricultural activities. The uncertain timing of the planting season due to changes in rainfall is one of the causes of the crisis, namely crop failure so that it is difficult for farmers to meet their food needs and poses a threat of food insecurity. One of the efforts that the community can do in facing the threat of a crisis is to preserve the food barn institution. The purpose of this study was to determine the role of food institutions in the community of rainfed rice farmers in Jati Agung District in dealing with the impacts of climate change. The research was conducted by survey method, using quantitative and qualitative data. Respondents and informants were selected by simple random sampling as many as 100 community members. The research location was chosen purposively in Marga Kaya Village, South Lampung. This study found that the institutional granary plays a role in social and economic aspects. The role of the food barn institution for the rainfed rice farming community is as a supporter of food availability, as a delay in selling, providing capital loans and a role in supporting the resilience of the farming community. Kata kunci: food barn, institution, rainfed rice farmer